Rewriting a History of Open Universities: (Hi)stories of Distance Teachers - Lee, Kyungmee (International Review of Research in Open and Distributed Learning, 2019)
This article reports eight distance teachers’ stories about teaching at two open universities over the past two decades with a focus on their perceptions and feelings about the changes in their teaching practice. This qualitative study employed a methodological approach called the autoethnographic interview, aiming to document more realistic histories of the open universities and to imagine a better future for those universities. As a result, the paper presents autobiographical narratives of distance teachers that dissent from the general historical accounts of open universities. These narratives are categorized into three interrelated themes: a) openness: excessive openness and a lost sense of mission; b) technological innovation: moving online and long-lasting resistance, and c) teaching: transactional interactions and feelings of loneliness. The paper then presents a discussion of useful implications for open universities, which can serve as a starting point for more meaningful discussions among distance educators in a time of change.